Older Patients' Views of Health Care Interactions in Ireland - Sarah Gibney; Tara Moore (SLACK Incorporated, 2018)
Background: Chronic and sensitive health conditions such as pain, urinary incontinence, and hearing loss are common but often untreated among older adults in Ireland, and many patients do not disclose these and other sensitive health issues to their health care provider. Objective: This study investigates the link between provider communication and older patients' perceived encouragement to talk about physical, social, sensitive, and emotional problems with their usual source of care (USC), be it a doctor or nurse. Methods: Data were from the Irish sample of the Survey of Health, Ageing and Retirement in Europe (SHARE; N = 720). Logistic regression models were used to estimate the association among (1) patient characteristics, (2) health care use, and (3) USC communication characteristics and the likelihood of feeling encouraged to talk about each health problem. Results are reported as odds ratios (OR) with confidence intervals at the 95% level. Key Results: More patients felt discouraged to talk about social (39%) and sensitive (42%) health problems with their USC compared with physical (18%) and emotional (29%) health problems. Many participants reported that their USC rarely or never explained the results of medical examinations (23.6%), explained different treatment options (26.2%), or listened to their opinions or preferences when making treatment decisions (29.1%). A USC "explaining test results" was associated with increased odds of feeling encouraged to discuss physical (OR = 2.82, 95% confidence interval [CI; 1.15, 6.91]) and social (OR = 2.02, 95% CI [1.01, 4.04]) problems. "Listening to patient preferences" was associated with increased odds of feeling encouraged to discuss physical (OR = 4.49; 95% CI [2.24-9.01]), emotional (OR = 2.31, 95% CI [1.27, 4.21]), and social (OR = 2.88, 95% CI [1.60, 5.18]) problems. Controlling for USC communication characteristics attenuated the association between lower educational attainment and perceived encouragement. Conclusions: An open and patient-centered communication style was associated with a greater sense of encouragement to discuss physical, emotional, and social health problems, particularly among older patients with lower levels of education.